Long-term assessment of the risk of spread in primary late-onset focal dystonia. Issue 4 (17th July 2007) - Abbruzzese, G; Berardelli, A; Girlanda, P; Marchese, R; Martino, D; Morgante, F; Avanzino, L; Colosimo, C; Defazio, G
Abstract : Background: Primary late-onset focal dystonias may spread over time to adjacent body regions, but differences in the risk of spread over time among the various focal forms and the influence of age at dystonia onset on the risk of spread are not well established. Methods: Patients presenting with primary late-onset focal blepharospasm (BSP, n = 124), cervical dystonia (CD, n = 73) and focal hand dystonia (FHD, n = 24) with 10 years or more of disease duration (mean ± SD, 15.3 (SD 4.9) years) were included in the study. The relationship between demographic/clinical variables and spread of dystonia was assessed by Kaplan–Meier survival curves and Cox proportional hazard regression models. Results: Patients starting with BSP, CD and FHD had similar age, sex and disease duration. Age at dystonia onset, age at initial spread and the risk of initial spread were significantly higher, whereas time elapsing from onset to initial spread was significantly lower in the BSP group than in those with onset in the neck or in the upper extremities. Conversely, these parameters were similar in the CD and FHD groups. The greater risk of spread in the BSP group was mainly evident in the first 5 years of history; thereafter, it declined and became similar to that of patients with CD/FHD. The difference in the risk of initial spread by site of onset was partly confounded by age at dystonia onset. Site of and age at dystonia onset, and age at first spread, were not significant predictors of the risk of a second spread. Conclusion: This study adds new insights into the phenomenon of spread of primary late-onset focal dystonia and provides the framework for future studies aimed at an indepth investigation of the mechanism(s) of spread.